Microcalorimetric studies of the growth of sulfate-reducing bacteria: comparison of the growth parameters of some Desulfovibrio species. - Traore, A S (1982)
We performed a comparative study of the growth energetics of some species of Desulfovibrio by measuring microcalorimetric and molar growth yield values. Lactate and pyruvate were used as energy sources for sulfate reduction. On lactate-sulfate media Desulfovibrio desulfuricans Norway, Desulfovibrio gigas, and Desulfovibrio africanus exhibited molar growth yields of 4.1 +/- 0.6, 3.7 +/- 1.7, and 1.8 +/- 0.1 g/mol, respectively, whereas on pyruvate-sulfate media the molar growth yields were higher (8.5 +/- 0.8, 7.7 +/- 1.6, and 3.5 +/- 0.5 g/mol, respectively). Thus, we found that D. africanus was the least efficient species in converting energy into cell material. The uncoupling of energy in this strain was obvious since its catabolic activities were high compared with those of the two other strains. The enthalpy changes associated with lactate and pyruvate metabolism were -49 +/- 0.7 and -70.2 +/- 6.0 jK/mol, respectively, for D. desulfuricans, -76.6 +/- 1.8 and -91.2 +/- 1.1 kJ/mol, respectively, for D. gigas, and -78.8 +/- 7.2 and -88.0 +/- 6.2 kJ/mol, respectively, for D. africanus. D. gigas and D. africanus produced only acetate, CO2 and hydrogen sulfide as metabolic end products. In addition to these normal end products, D. desulfuricans Norway produced a small amount of butanol. This butanol production was interpreted as reflecting a regulatory system of electron flow during the catabolism of both substrates. Such metabolism was comparable to that reported for D. vulgaris, which lost part of the reducing power of its energy sources through hydrogen evolution.